Effect of Task-Specific Training on Trunk Control and Balance in Patients with Subacute Stroke - Mohamed E. Khallaf (Neurology Research International)
Objectives. Impairment of static and dynamic posture control is common after stroke. It is found to be a predictor and an essential component for balance, walking ability, and activities of daily living (ADL) outcomes. Studies investigating effect of physical therapy techniques with an aim to improve trunk function after stroke are limited. This study aimed at studying the effect of task-specific training on trunk control and balance in patients with subacute stroke. Methods. In this randomized controlled trail, thirty-four patients were alienated into two equal groups. The study group (n = 17) received task-specific training, and the control group (n = 17) received conventional physical therapy based on the neurodevelopmental technique. Task-specific training was applied through two phases with criteria of progression based on Chedoke–McMaster Stroke Assessment postural control stages. The interventions were applied in a dosage of 60 min per session, three times a week for ten weeks. Static and dynamic balance were measured by the trunk impairment scale (TIS), postural assessment scale (PAS), and functional reach test (FRT). Laser-guided digital goniometer was used to measure the trunk ranges of motions (ROM) as a secondary outcome. Results. Significant differences between the baseline and the follow-up measures including TIS, PAS, FRT, and trunk (ROM) were found in both groups (P≤0.05). In-between group comparison also showed significant differences between the results of both groups indicating more improvements among patients representing the study group. Conclusion. Task-specific training may be effective in improving the static and dynamic postural control and trunk ranges of motion among subacute stroke patients.